OP18 Evaluating the impact of the english health inequalities strategy on socioeconomic inequalities in the regional infant mortality rate. (September 2018) - Robinson, TJ; Barr, B; Brown, HW; Fraser, L; Norman, P; Bambra, C
Abstract : Background: Following the election of a Labour government in 1997 on a mandate that included a commitment to reducing health inequalities (HI) and implementing evidence-based policy, the UK became the first European country in which policy-makers systematically and explicitly attempted to reduce inequalities in health. One explicit target was to reduce socioeconomic disparities in infant mortality. However, it remains unclear whether the HI strategy had an impact on socioeconomic geographical inequalities in the infant mortality rate (IMR). We investigated whether the period of the HI strategy was associated with a change in the difference in the IMR between the most disadvantaged local authorities and the country as a whole compared with trends before and after the strategy. Methods: We used data from the UK data achieve and the ONS on the annual number of births and infant deaths in 323 local authority areas across England from 1983–2016. We initially calculated the IMR in the most deprived group of local authorities and the rest of England from 1983 to 2016, and the relative and absolute differences between these groups to investigate trends in inequalities before, during and after the strategy was introduced. We then used the panel of data to estimate segmented fixed effects regression models, including linear spline terms for time with two breakpoints at the beginning and end of the strategy period and an interaction term between the time trend and a dummy variable indicating the deprived groups of local authorities. Results: Prelimary results show that before the HI strategy, the relative gap in the IMR increased at a rate of 1.3% each year (95% confidence interval 0.8% to 1.8%). During the strategy period this trend reversed and the relative gap in the IMR decreased at a rate of 1.7% each year (95% confidence interval 0.7% to 2.8%). Since the end of the policy period, the relative gap in the IMR has continued to decrease (at a rate of 1.3% each year), however this change was found to not be statistically significant (95% CI −3.7% to 1.1%). Conclusion: The English HI strategy was associated with a small decline in relative geographical inequalities in the IMR, reversing a previously increasing trend. This result was found to be statistically significant (p<0.001). Future work will test the robustness of these results, through the use of different econometric methods (including Poisson regression models) and the inclusion of a number of controlling variables.